Pembuatan, Karakterisasi, dan Optimasi Nanopartikel Gelasi Ionik Ekstrak Kering Rimpang Temulawak (Curcuma xanthorrhiza R.) menggunakan Rancangan Faktorial 22 - Moch Futuchul Arifin; Yuslia Noviani; Safira Nafisa; Agisha Sheilabel (Fakultas Farmasi Universitas Pancasila, 2022)
Temulawak rhizome (Curcuma xanthorrhiza R.) is efficacious as antidiabetic because it has curcuminoid compounds. The aim of the research was to make, characterize, and optimize the nanoparticle formula of dried temulawak rhizome extract. The rhizomes were macerated using 96% ethanol. The curcuminoid content of the thick extract was determined using a spectrophotometer and dried extract using a spray dryer. The dried extract was formulated into nanosuspension using ionic gelation method by mixing a concentration of 0.1–0.5% dried extract with a mixture of 0.2% chitosan and 0.1% sodium tripolyphosphate in a 2:1–5:1 ratio. Characterization was carried out including: particle morphology, particle size, polydispersity index, zeta potential, and entrapment efficiency. Response data were analyzed by factorial 22 design using Minitab18 software to determine the optimum formula. The concentration of curcuminoids in the thick extract was 15.96%. The morphology of the nanosuspension was spherical, with a particle size of 114.7–399.3 nm, a polydispersity index of 0.429–0.597, a zeta potential of 35.1–48.6 mV, and an entrapment efficiency of 61.08–73.37%. The optimum formula was obtained with a composition of 0.44% extract and chitosan: Na-TPP (2:1) with a desirability value, d= 0.8984. It can be concluded that the factorial design of 22 can be used to determine the optimum formula for dried extract of temulawak rhizome using the ionic gelation method.